Loss of electrically active myocardium during anterior infarction in man. - Selwyn, A P (1977)
A method has been developed of praecordial mapping of changes in R/S ratio and the appearance of Q waves in acute myocardial infarction. Observation of the serial changes in R and Q waves in 40 patients with uncomplicated anterior infarction shows that the loss of electrically active myocardium occurs within 6 hours of the onset of chest pain. Complications, such as recurrent chest pain, associated with extension of myocardial necrosis can be identified and assessed. The total praecordial changes in R/S ratio and Q wave amplitude correlate with the total MB fraction of creatine kinase activity released into the plasma in 20 patients after uncomplicated anterior infarction. This technique for identifying those factors that may modify the progressive loss of active myocardium in the early phase of acute infarction of the heart is noninvasive and repeatable.